Pembuatan Konten di Reels Instagram Sebagai Media Iklan pada Aura Park Malang - Chandra Arga Saputra; Fatkhur Rochman; Maskur (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aimed to make content on the Instagram reels feature as an advertising medium to promote Aura Park Malang housing using the Adobe Premier Pro Application. The study used the Action Research method consisting of planning, action, observation, and reflection. The assessment of content effectiveness was carried out through the Grammar of Edit approach for the quality of video marketing content, as well as the EPIC Model (Empathy, Persuasion, Impact, Communication) to measure the effectiveness of video marketing content. The sample in this study consisted of 11 respondents, including owners, employees, marketing experts, computer experts, and prospective consumers. The results of the questionnaire analysis on Grammar of Edit showed a score of 85%, this is categorized as feasible and meets the standards in video quality. While the results of the analysis on the EPIC rate were 4.4 on video 1, 4.4 on video 2, 4.3 on video 3, 4.3 on video 4 and 4.2 on video 5. There was an increase in the effectiveness score on video 5 after revisions were made in the second cycle by obtaining an average EPIC score of 4.3. Therefore, all video content are included in the "very good" category. This means that based on the results of the study, it can be concluded that video marketing content is included in the very effective category. Thust it is recommended that the business apply the videos an the advertising media at Aura Park Malang.   Keywords: Adobe Premiere Pro; EPIC Model; Instagram Reels   ABSTRAK Penelitian ini bertujuan untuk membuat konten di reels instagram sebagai media iklan untuk perumahan Aura Park Malang dengan menggunakan Aplikasi Adobe Premier Pro. Pada penelitian menggunakan metode Action Research, yang terdiri dari perencanaan, tindakan, observasi, dan refleksi. Penilaian efektivitas konten dilakukan melalui pendekatan Grammar of Edit untuk kualitas konten video marketing, serta EPIC Model (Empathy, Persuasion, Impact, Communication) untuk mengukur efektivitas konten video marketing. Sampel dalam penelitian ini terdiri dari 11 responden, yang meliputi pemilik, karyawan, ahli pemasaran, ahli komputer, serta calon konsumen. Hasil analisis kuesioner pada Grammar of Edit mendapatkan skor 85% dikategorikan layak dan memenuhi standar dalam kualitas video. Sedangkan hasil analisis pada EPIC rate sebesar 4.4 pada video 1, 4.4 pada video 2, 4.3 pada video 3, 4.3 pada video 4 dan 4.2 pada video 5. Terdapat peningkatan skor efektivitas pada video 5 setelah dilakukan revisi pada siklus kedua dengan memperoleh EPIC rate sebesar 4.3. Oleh karena itu seluruh konten video marketing termasuk kategori “sangat baik”. Artinya Berdasarkan hasil penelitian dapat disimpulkan bahwa konten video marketing termasuk dalam kategori sangat efektif. Sehingga diharapkan dapat menjadi media iklan pada Aura Park Malang.